Necrotic skin lesion in a dog attributed to Loxosceles (brown spider) bite: A case report - Machado, Luiz Henrique De Araújo [UNESP]; Antunes, M. I.P.P. [UNESP]; Mazini, A. M. [UNESP]; Sakate, M. [UNESP]; Torres-Neto, R. [UNESP]; Fabris, V. E. [UNESP]; Vailati, M. C.F. [UNESP]; Lourenço, M. L.G. [UNESP] (FapUNIFESP (SciELO), 2009)
Envenomations caused by Loxosceles (brown spider) have been reported throughout the world. Clinical signs associated to bites of these spiders involve dermonecrotic lesions and intense local inflammatory response, besides systemic manifestations such as intravascular hemolysis, thrombocytopenia, disseminated intravascular coagulation and acute renal failure. The present study aimed to report and to describe dermonecrotic lesions probably caused by a Loxosceles envenomation in a four year-old poodle female dog, treated at the Dermatology Service of the Veterinary Hospital of the Veterinary Medicine and Animal Husbandry School, São Paulo State University, Botucatu, Brazil. Initially, the animal presented two skin lesions with blackish aspect that evolved into ulcerative crusts. The owner reported the presence of a brown spider near the place where the animal spent most of the time. Histological examination of lesions revealed necrosis of the epidermis extending to adnexa and panniculi, which is compatible with Loxosceles bite reaction. The animal was treated with systemic antibiotic and local curatives. Lesions healed by second intention in two months.
Keywords: Dermonecrotic toxin; Dogs; Loxosceles